2017
DOI: 10.1002/pon.4598
|View full text |Cite
|
Sign up to set email alerts
|

Mobile‐based patient‐provider communication in cancer survivors: The roles of health literacy and patient activation

Abstract: MBPPC alone does not directly result in better emotional health outcomes; health literacy is the key to realize its health benefits; patient activation significantly strengthens the effects of MBPPC. As we embrace the mHealth movement, innovative programs are needed to promote MBPPC, and improve health literacy and activation of cancer survivors, particularly in underserved communities, to reduce health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Studies have shown that when doctors provided their patients with useful health information, while responding to their emotions, patients experienced a sense of self-control and greater hope. This has had a directly positive impact on their quality of life as well as their survival [27]. The method of entering into a relationship with the patient has therefore proved decisive, with the possibility that the caregiver could let the patient engage and be involved in his/her own care continuum.…”
Section: The Need To Change Practitioners' Attitudes To Enable Them Tmentioning
confidence: 99%
“…Studies have shown that when doctors provided their patients with useful health information, while responding to their emotions, patients experienced a sense of self-control and greater hope. This has had a directly positive impact on their quality of life as well as their survival [27]. The method of entering into a relationship with the patient has therefore proved decisive, with the possibility that the caregiver could let the patient engage and be involved in his/her own care continuum.…”
Section: The Need To Change Practitioners' Attitudes To Enable Them Tmentioning
confidence: 99%
“…Health literacy, an individual's capacity to obtain and use health information to adopt new health‐related skills or make health‐related decisions, may influence intervention uptake and adoption . Further evidence suggests health literacy may mediate the effect of technology‐based intervention on emotional outcomes among cancer survivors …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Further evidence suggests health literacy may mediate the effect of technology-based intervention on emotional outcomes among cancer survivors. 21 To our knowledge, little research has been carried out to experimentally evaluate commercially available mindfulness apps. Randomized controlled trials have examined commercial mindfulness apps in the context of health-related QOL, 22 stress, 23 depression, 24 compassion, 25 emotional wellbeing, 13 and executive functioning, 26 among non-clinical populations, with promising results.…”
mentioning
confidence: 99%
“…Individuals generate and share their own health-related experiences [8], such as surgery process, medication experience, and treatment plan. Health care professionals use social media to interact with patients to improve social support and health education [9]. These practices are now changing our perception of the quality of online health information access and sources; 61% of American adults look online for health information and 37% have accessed user-generated health information online [10].…”
Section: Current Practicesmentioning
confidence: 99%
“…To improve health literacy, health organizations are adopting social media as a means to facilitate further communication. For example, health organizations have started to provide information about health services available at local health departments [21] and promote health education [9]. Similarly, social media can be used to amplify community outreach.…”
Section: Other Opportunitiesmentioning
confidence: 99%